Strategi Pencegahan Stunting melalui Rumah Desa Sehat dan Pemanfaatan Lahan Pekarangan Rumah di Desa Karya Indah Kecamatan Buntulia Kabupaten Pohuwato - Kadir, Rosma; Lantowa, Jafar (Universitas Negeri Gorontalo, 2019)
School children are at a rapid development stage in their intellectual and skill processes and are beginning to have vigorous physical activities. To support the development and physical activity, school children need various kinds of nutrients in sufficient quantities in order to grow and develop properly, because the role of nutrition greatly determines the child's health condition.In this regard, many direct factors are affecting nutritional status, including food consumption and infectious diseases. Moreover, several indirect factors, such as knowledge, education, income level, parental education, and family size, also affected the nutritional status. In developing countries, including Indonesia, nutrition is becoming more critical in terms of public health because malnutrition can reduce immunity to several diseases, especially infectious diseases.This community service program aims to increase education and provide information about stunting through the dissemination of stunting prevention and fostering the creativity of the community through the utilization of the home yard. The implementation methods employed includeddissemination, the use of Poskesdes as a Healthy Village House, coaching, and community empowerment. Thematic Community Service Program outputs are dissemination activities, the formation of Healthy Village Houses and modules on the use of house yards, and the formation of garden models, which are the results of the utilization of house yards that can be emulated by people who want to use their houses as gardens. The advice given regarding this Community Service Program is that the local government needs to support the stunting prevention in the village, especially in Karya Indah Village. Moreover, awareness is needed from village officials, health cadres, and the community in managing Poskesdes as a Healthy Village Home. Guidance and support from village officials and youth organizations are also needed for the community regarding the utilization of home yards